Spikes in acute workload are associated with increased injury risk in elite cricket fast bowlers - Hulin, Billy T; Gabbett, Tim J; Blanch, Peter; Chapman, Paul; Bailey, David; Orchard, John W (British journal of sports medicine, 2014)
Objective To determine if the comparison of acute and chronic workload is associated with increased injury risk in elite cricket fast bowlers. Methods Data were collected from 28 fast bowlers who completed a total of 43 individual seasons over a 6-year period. Workloads were estimated by summarising the total number of balls bowled per week (external workload), and by multiplying the session rating of perceived exertion by the session duration (internal workload). One-week data (acute workload), together with 4-week rolling average data (chronic workload), were calculated for external and internal workloads. The size of the acute workload in relation to the chronic workload provided either a negative or positive training-stress balance. Results A negative training-stress balance was associated with an increased risk of injury in the week after exposure, for internal workload (relative risk (RR)=2.2 (CI 1.91 to 2.53), p=0.009), and external workload (RR=2.1 (CI 1.81 to 2.44), p=0.01). Fast bowlers with an internal workload training-stress balance of greater than 200% had a RR of injury of 4.5 (CI 3.43 to 5.90, p=0.009) compared with those with a training-stress balance between 50% and 99%. Fast bowlers with an external workload training-stress balance of more than 200% had a RR of injury of 3.3 (CI 1.50 to 7.25, p=0.033) in comparison to fast bowlers with an external workload training-stress balance between 50% and 99%. Conclusions These findings demonstrate that large increases in acute workload are associated with increased injury risk in elite cricket fast bowlers.